Seed longevity and fire: germination responses of an exotic perennial herb in NW Patagonian grasslands (Argentina) - Franzese, Jorgelina (2011)
Fire affects grassland composition by selectively influencing recruitment. Some exoticspecies can increase their abundance as a consequence of fire-stimulated seedgermination, but response may depend on seed age. Rumex acetosella L. (Polygonaceae,sheep?s sorrel) is a cosmopolitan herb that has invaded NW Patagonia?s grasslands.This species forms persistent soil seed banks and increases after disturbances,particularly fire. We studied how fire and seed longevity influence R. acetosella germination.In 2008, we conducted laboratory experiments where we exposed different-aged seeds (up to 19 years old) to heat, smoke, charcoal, ash and controltreatments. Total percentage germination and mean germination time depended onboth seed age and fire treatment. Germination of younger seeds decreased withincreasing temperature. There was no general pattern in germination responses ofdifferent-aged seeds to smoke, charcoal and ash. While smoke improved the germinationof fresh seeds, charcoal decreased germination. Germination of untreatedseeds was negatively correlated with seed age, and mean germination time increasedwith seed age. In most treatments, fresh seeds had lower germination than 1?5-year-old seeds, indicating an after-ripening requirement. Smoke stimulates R. acetosellagermination, causing successful recruitment during post-fire conditions. Freshseeds are particularly responsive to fire factors, possibly because they have not experiencedphysical degradation and are more receptive to environmental stimuli.Knowing the colonisation potential from the soil seed bank of this species duringpost-fire conditions will allow us to predict their impact on native communities.